Ectopic ACTH Production Leading to Diagnosis of Underlying Medullary Thyroid Carcinoma. (8th April 2016) - Matheny, Leslee N.; Wilson, Jessica R.; Baum, Howard B. A.
Medullary thyroid carcinoma (MTC) has been described as a source of ectopic ACTH secretion in patients with Cushing's syndrome. This is an infrequent association, occurring in less than 1% of MTC cases. Among these, it is even more unusual for an initial diagnosis of hypercortisolism to lead to the discovery of underlying MTC. Here we present a case of a patient with weakness, diarrhea, and hypokalemia who was found first to have Cushing's syndrome and later diagnosed with metastatic MTC. The patient was treated initially with oral agents to control his hypercortisolism, then with an etomidate infusion after experiencing intestinal perforation. He also received vandetanib therapy targeting his underlying malignancy, as this has been shown to reverse clinical signs of Cushing's syndrome in patients with MTC and subsequent ectopic ACTH secretion. Bilateral adrenalectomy was ultimately required. Medullary thyroid carcinoma should be considered in patients presenting with Cushing's syndrome due to ectopic ACTH secretion, and a multimodality treatment approach is often required.